2016
DOI: 10.1097/01.naj.0000490182.21432.85
|View full text |Cite
|
Sign up to set email alerts
|

Health Care Worker Fatigue

Abstract: The Pennsylvania Patient Safety Reporting System is a confidential, statewide Internet reporting system to which all Pennsylvania hospitals, outpatient-surgery facilities, birthing centers, and abortion facilities must file information on incidents and serious events.Safety Monitor is a column from Pennsylvania's Patient Safety Authority, the authority that informs nurses on issues that can affect patient safety and presents strategies they can easily integrate into practice. For more information on the author… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 6 publications
0
8
0
Order By: Relevance
“…These results were confirmed through sensitivity analyses using several cutoff values for surgeon experience. Accordingly, studies have shown that moderate levels of fatigue produce higher levels of performance impairment compared to proscribed levels of alcohol intoxication [35] and that fatigue may cause medical incidences or accidents [36]. Moreover, evidence has suggested that unexpected challenges tended to emerge with technical immaturity and when introducing a new modality [37,38].…”
Section: Discussionmentioning
confidence: 99%
“…These results were confirmed through sensitivity analyses using several cutoff values for surgeon experience. Accordingly, studies have shown that moderate levels of fatigue produce higher levels of performance impairment compared to proscribed levels of alcohol intoxication [35] and that fatigue may cause medical incidences or accidents [36]. Moreover, evidence has suggested that unexpected challenges tended to emerge with technical immaturity and when introducing a new modality [37,38].…”
Section: Discussionmentioning
confidence: 99%
“…24 Medication, diagnostic, and procedural errors are the most common errors that occur as a result of health care worker fatigue. 25…”
Section: Potential Impact On Patient Carementioning
confidence: 99%
“…[3][4][5] Fatigue among nurses is particularly important because of its negative impact on performance. 3,6 Fatigue is associated with errors in various patient care activities, including medication administration. 6,7 Fatigue reduces cognitive and physical abilities not only threatening patient safety but also personal safety [5][6][7][8] and has been attributed to 13% of all workplace injuries.…”
mentioning
confidence: 99%
“…3,6 Fatigue is associated with errors in various patient care activities, including medication administration. 6,7 Fatigue reduces cognitive and physical abilities not only threatening patient safety but also personal safety [5][6][7][8] and has been attributed to 13% of all workplace injuries. 8 Furthermore, fatigue negatively affects quality of life for nurses.…”
mentioning
confidence: 99%